Impact of occupational cadmium exposure on bone in sewage workers - Taha, Mona M (Int J Occup Environ Health, 2018)
Cadmium (Cd) is one of the environmental risk factors for bone loss. The present study included 40 sewage workers occupationally exposed to Cd. Forty nonexposed men were included as a control group. Current smokers represented 65% and 47.5% of the exposed and control groups, respectively. The study aimed to investigate the hazard of occupational Cd exposure on bone health. This was achieved through measuring serum and urinary Cd, and calcium (Ca), in addition to serum osteoprotegerin (OPG) and estrogen receptor-α gene. Results showed significant elevation in serum Cd, OPG, and urinary Ca levels in the exposed compared to the controls. Bony aches and joint pain were more prevalent among the exposed workers. Serum and urinary Cd increased in exposed smokers relative to control smokers. Also, serum OPG levels showed significant rise among exposed smoker and nonsmoker compared to control smoker and nonsmoker groups. Serum Cd level increased significantly in PP and pp genotypes in exposed workers compared to controls, while elevated levels of serum OPG was observed in PP and Pp genotypes in exposed workers relative to controls. Urinary Cd exhibited significant rise in both PP and pp genotypes in exposed workers, while Ca excretion was elevated in pp genotype only. The study reflected an association of genetic predisposition and Cd exposure in progression of osteoporosis. Further research is needed to explain the mechanisms of Cd impact on bone. The role of smoking is important and hence smoking cessation programs are essential for sewage workers.